ACTUAL PROBLEMS OF FURTHER ANTI-CORRUPTION IN KAZAKHSTAN - Ramazan Tuyakovich Нуртаев (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article deals with topical issues of further intensification of the struggle against corruption in Kazakhstan due to the correct psycho-social and legal assessment of the phenomenon of corruption from the perspective of modern realities of life and the search for ways to improve the existing criminal legislation governing responsibility for corruption.